STRATEGI KOMUNIKASI BIDAN MUGI RAHAYUDALAM PENGUATAN AKIDAH IBU HAMIL MELALUI KEGIATAN “BUMIL AYO NGAJI” 2025 - Reviska Oktaviana Diva; Siti Nur Fadlilah (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2026)
This study aims to answer the question of how Bidan Mugi Rahayu’s communication strategy is implemented in strengthening the faith (aqidah) of pregnant women through the Bumil Ayo Ngaji 2025 program. This research employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The findings reveal Bidan Mugi Rahayu’s communication strategy can be analyzed using Anwar Arifin’s four components of communication strategy. First, understanding the audience, Bidan Mugi Rahayu understands the physical and emotional conditions of pregnant women as the main target. Second, massage formulation, in the process of formulating massages, Bidan Mugi Rahayu conducts surveys to identify the needs of pregnant women, continues her midwifery education, and read research findings relevant to pregnancy and childbirth. Third, method determination, Bidan Mugi Rahayu applies informative, educative, and persuasive methods. Fourth, media selection, the media used include Zoom, YouTube, and Microsoft PowerPoint. Therefore, the communication strategy used by Bidan Mugi Rahayu fulfills the principles of communication functions according to Effendi Gazali, namely to educate and to influence, educating and influencing pregnant women’ perspectives to view pregnancy as a form of worship rather than merely a biological event, and to help them avoid trauma during pregnancy and childbirth.